A phylogenomic study of Iridaceae Juss. based on complete plastid genome sequences - Kamra, Kashish; Jung, Joonhyung; Kim, Joo-Hwan (Frontiers in Plant Science, 2023)
The plastid genome has proven to be an effective tool for examining deep correlations in plant phylogenetics owing to its highly conserved structure, uniparental inheritance, and limited variation in evolutionary rates. Iridaceae, comprising more than 2,000 species, includes numerous economically significant taxa that are frequently utilised in food industries, medicines, and for ornamental and horticulture purposes. Molecular studies on chloroplast DNA have confirmed the position of this family in the order Asparagales with non-asparagoids. The current subfamilial classification of Iridaceae recognises seven subfamilies: Isophysioideae, Nivenioideae, Iridoideae, Crocoideae, Geosiridaceae, Aristeoideae, and Patersonioideae, which are supported by limited plastid DNA regions. To date, no comparative phylogenomic studies have been conducted on the family Iridaceae. We assembled and annotated (de novo) the plastid genomes of 24 taxa together with seven published species representing all the seven subfamilies of Iridaceae and performed comparative genomics using the Illumina MiSeq platform. The plastomes of the autotrophic Iridaceae represent 79 protein-coding, 30 tRNA, and 4 rRNA genes, with lengths ranging from 150,062 bp to 164,622 bp. Phylogenetic analysis of the plastome sequences based on maximum parsimony, maximum likelihood, and Bayesian inference analyses suggested that Watsonia and Gladiolus were closely related, supported by strong support values, which differ considerably from recent phylogenetic studies. In addition, we identified genomic events, such as sequence inversions, deletions, mutations, and pseudogenisation, in some species. Furthermore, the largest nucleotide variability was found in the seven plastome regions, which can be used in future phylogenetic studies. Notably, three subfamilies, Crocoideae, Nivenioideae, and Aristeoideae, shared a common ycf2 gene locus deletion. Our study is a preliminary report of a comparative study of the complete plastid genomes of 7/7 subfamilies and 9/10 tribes, elucidating the structural characteristics and shedding light on plastome evolution and phylogenetic relationships within Iridaceae. Additionally, further research is required to update the relative position of Watsonia within the tribal classification of the subfamily Crocoideae.